2022
DOI: 10.1139/cjm-2021-0360
|View full text |Cite
|
Sign up to set email alerts
|

Choice of cover crop influences soil fungal and bacterial communities in Prince Edward Island, Canada

Abstract: Soil fungal and bacterial communities play various roles in agroecosystems and are significantly influenced by agricultural management practices. Currently, little is known about the effects of selected cover crops on soil fungal and bacterial communities in no-till systems. In this study, eight cover crops, three mixed crops, and an unmanaged fallow control were evaluated over two years for their effects on the soil microbiome. ITS and 16S rRNA amplicon sequencing was performed to characterize fungal and bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Among 30 most abundant fungal genera in the intercropping area, 5 genera were significantly increased with Siratro cover crop compared to conventional tillage, including Acremonium that could be contributing to the increase in saprotrophs_symbiotrophs. Also among those, 5 genera were significantly decreased with Siratro Benitez et al (2016) where legume cover crops increased symbiotrophs, and Aiyer et al (2022) where a sorghum-sudangrass cover crop decreased pathotrophs and increased symbiotrophs while an alfalfa cover crop increased pathotrophs. Thus, the effect of cover crops on soil fungal guilds appears to highly dependent upon the type of plant used.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Among 30 most abundant fungal genera in the intercropping area, 5 genera were significantly increased with Siratro cover crop compared to conventional tillage, including Acremonium that could be contributing to the increase in saprotrophs_symbiotrophs. Also among those, 5 genera were significantly decreased with Siratro Benitez et al (2016) where legume cover crops increased symbiotrophs, and Aiyer et al (2022) where a sorghum-sudangrass cover crop decreased pathotrophs and increased symbiotrophs while an alfalfa cover crop increased pathotrophs. Thus, the effect of cover crops on soil fungal guilds appears to highly dependent upon the type of plant used.…”
Section: Discussionmentioning
confidence: 97%
“…However, less abundant fungal genera would also have an impact. Some other examples where cover crops affected the abundance of soil fungal guilds are Wei et al (2021) where grass cover crops increased pathotrophs and decreased saprotrophs, Benitez et al (2016) where legume cover crops increased symbiotrophs, and Aiyer et al (2022) where a sorghum–sudangrass cover crop decreased pathotrophs and increased symbiotrophs while an alfalfa cover crop increased pathotrophs. Thus, the effect of cover crops on soil fungal guilds appears to highly dependent upon the type of plant used.…”
Section: Discussionmentioning
confidence: 99%
“…As such, choosing the cover crop that minimizes loss and potentially contributes to better productivity in subsequent years becomes critical. The cover crop identity within a rotation can have a significant influence on the soil microbial community composition [ 11 , 13 ]. For example, an increase in the abundance of plant pathogenic fungi has been reported following crops such as oilseed radish ( Raphanus sativus L.), alfalfa ( Medicago sativa L.), and phacelia ( Phacelia tanacetifolia Benth.)…”
Section: Introductionmentioning
confidence: 99%
“…For example, an increase in the abundance of plant pathogenic fungi has been reported following crops such as oilseed radish ( Raphanus sativus L.), alfalfa ( Medicago sativa L.), and phacelia ( Phacelia tanacetifolia Benth.) [ 13 ]. Bainard et al [ 14 ], found that the sequential planting of pulse crops can increase the population of certain soil-borne pathogens, including several Fusarium spp.. Buckwheat ( Fagopyrum esculentum Moench.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation